THE ROLE OF THE ACTOR AND THE ARTIST IN THE PROCESS OF IMAGE CREATION IN PUPPET THEATRE - G.Abdumutalibova (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: This article analyzes the creative characteristics of actors and artists in the process of creating a character in puppet theater. It examines the specific features of puppet theater as a performing art, the role of the actor in bringing the character to life on stage through movement, gestures, and voice, as well as the artist’s contribution to the visual representation through design, color, and construction. The article also discusses the collaboration between these two creators and the process of forming a complete artistic character on stage.